Thermodynamic performance evaluation of solar and other thermal power generation systems: A review. (October 2015) - Gupta, M.K.; Kaushik, S.C.; Ranjan, K.R.; Panwar, N.L.; Reddy, V. Siva; Tyagi, S.K.
Abstract: In this communication, detailed review of the solar thermal power plants based on the available solar concentrator systems like parabolic trough, parabolic dish, central tower, linear Fresnel reflector system are reported. The aim of the paper is to summarize overall research work being carried out worldwide on the thermodynamic performance evaluation of solar and other thermal power generation systems using different thermodynamic cycles. An attempt has also been made to assess as well as compare the energetic and exergetic performance of such thermal power generation systems. It has been observed that the efficiencies of the solar concentrator aided coal fired thermal power plant, and combined-cycle power plants are higher as compared to a solar alone thermal power plants. Furthermore, there is much scope in the areas of solar aided thermal power generation for further research with the aim of quantifying energy and exergy losses, and exergy destructions in the components of the solar thermal power generation systems.